Development of chick retina cells in culture: cobalt entry through AMPA receptors and expression of GluR4 AMPA receptor subunit - Cristóvão, Armando J. (2003)
The functionality of [alpha]-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors in chick embryo retina cells during development in vitro was studied by using Co2+ uptake, and these data were correlated with the expression of the AMPA receptor subunit GluR4. We found that at 5 h in vitro only a small number of cells took up Co2+ upon stimulation with 100 [mu]M kainate or other AMPA receptor agonists, in the presence of cyclothiazide (CTZ), to inhibit desensitisation. The number of cells sensitive to kainate increased from 5 h in vitro to 3 days in vitro (DIV), and remained relatively constant until 14 DIV. When the cells were stimulated with (2S,4S)-4-methylglutamic acid (30 [mu]M), a specific kainate receptor agonist, after inhibiting desensitisation with concanavalin A, we did not observe an increase in the number of cells responding, as compared to the control. The expression of the AMPA receptor subunit GluR4 during development was detected by immunofluorescence mainly at the perinuclear region of the cells, and the number of positive cells increased from 5 h in vitro to 7 DIV, and remained relatively constant until 14 DIV. The results suggest that AMPA receptors can be functionally active at early embryonic stages (5 h in vitro) in cultured retinal neurons, although in only a few cells, before synapse formation (E12). The localisation of GluR4 was well correlated with Co2+ entry, since the strongest GluR4 immunoreactivity was found in the regions that showed the most intense labelling with Co2+. Finally, we found that the expression levels of GluR4 at the neurites increased between 5 h in vitro and 7 DIV, near the period of synapse formation.